Exercise training decreases activation of the mitochondrial fission protein dynamin-related protein-1 in insulin-resistant human skeletal muscle - Fealy, Ciaran E. (American Physiological Society, 2014)
Defects in mitochondrial dynamics, the processes of fission, fusion, and mitochondrial autophagy, may contribute to metabolic disease including type 2 diabetes. Dynamin-related protein-1 (Drp1) is a GTPase protein that plays a central role in mitochondrial fission. We hypothesized that aerobic exercise training would decrease Drp1 Ser(616) phosphorylation and increase fat oxidation and insulin sensitivity in obese (body mass index: 34.6 ± 0.8 kg/m(2)) insulin-resistant adults. Seventeen subjects performed supervised exercise for 60 min/day, 5 days/wk at 80–85% of maximal heart rate for 12 wk. Insulin sensitivity was measured by hyperinsulinemic-euglycemic clamp, and fat oxidation was determined by indirect calorimetry. Skeletal muscle biopsies were obtained from the vastus lateralis muscle before and after the 12-wk program. The exercise intervention increased insulin sensitivity 2.1 ± 0.2-fold (P < 0.01) and fat oxidation 1.3 ± 0.3-fold (P < 0.01). Phosphorylation of Drp1 at Ser(616) was decreased (pre vs. post: 0.81 ± 0.15 vs. 0.58 ± 0.14 arbitrary units; P < 0.05) following the intervention. Furthermore, reductions in Drp1 Ser(616) phosphorylation were negatively correlated with increases in fat oxidation (r = −0.58; P < 0.05) and insulin sensitivity (rho = −0.52; P < 0.05). We also examined expression of genes related to mitochondrial dynamics. Dynamin1-like protein (DNM1L; P < 0.01), the gene that codes for Drp1, and Optic atrophy 1 (OPA1; P = 0.05) were significantly upregulated following the intervention, while there was a trend towards an increase in expression of both mitofusin protein MFN1 (P = 0.08) and MFN2 (P = 0.07). These are the first data to suggest that lifestyle-mediated improvements in substrate metabolism and insulin sensitivity in obese insulin-resistant adults may be regulated through decreased activation of the mitochondrial fission protein Drp1.